CBP and p300 acetylate PCNA to link its degradation with nucleotide excision repair synthesis. Issue 13 (17th June 2014) - Cazzalini, Ornella; Sommatis, Sabrina; Tillhon, Micol; Dutto, Ilaria; Bachi, Angela; Rapp, Alexander; Nardo, Tiziana; Scovassi, A. Ivana; Necchi, Daniela; Cardoso, M. Cristina; Stivala, Lucia A.; Prosperi, Ennio
Abstract: The proliferating cell nuclear antigen (PCNA) protein serves as a molecular platform recruiting and coordinating the activity of factors involved in multiple deoxyribonucleic acid (DNA) transactions. To avoid dangerous genome instability, it is necessary to prevent excessive retention of PCNA on chromatin. Although PCNA functions during DNA replication appear to be regulated by different post-translational modifications, the mechanism regulating PCNA removal and degradation after nucleotide excision repair (NER) is unknown. Here we report that CREB-binding protein (CBP), and less efficiently p300, acetylated PCNA at lysine (Lys) residues Lys13, 14, 77 and 80, to promote removal of chromatin-bound PCNA and its degradation during NER. Mutation of these residues resulted in impaired DNA replication and repair, enhanced the sensitivity to ultraviolet radiation, and prevented proteolytic degradation of PCNA after DNA damage. Depletion of both CBP and p300, or failure to load PCNA on DNA in NER deficient cells, prevented PCNA acetylation and degradation, while proteasome inhibition resulted in accumulation of acetylated PCNA. These results define a CBP and p300-dependent mechanism for PCNA acetylation after DNA damage, linking DNA repair synthesis with removal of chromatin-bound PCNA and its degradation, to ensure genome stability.